Producción y Comercialización de artesanías tradicionales en la Asociación de Artesanos Makiwan Rurashka en la ciudad de Riobamba - Sánchez Guerra, Estefano José (2025)
The production and commercialization of traditional products by the Makiwan Rurashka Artisan Association in Riobamba, composed of 11 artisans who own their own businesses, is focused on improving their positioning locally and nationally. To increase production and sales in the market, it is necessary to adopt marketing strategies that enhance sales performance. This study outlined objectives and hypotheses to guide the research and ensure that the marketing strategies produce the desired results for the ventures of the Makiwan Rurashka Artisan Association members. The variables are described in the theoretical section, providing the necessary knowledge to develop commercialization strategies. In the methodological section, the hypothetical-deductive method was chosen, which allows the verification or refutation of the proposed hypotheses through data collection, analysis, and results presentation. Field and descriptive research methods were used, allowing the study of the investigated phenomenon and addressing the problem outlined in this research. In the survey section, the levels of production and commercialization of traditional products made by the 11 Makiwan Rurashka Artisan Association members in the city of Riobamba are analyzed